Modeling latent changes: A case of perceived competence measures - Buško, Vesna (Array, 2005)
Intraindividual variations in perceived self-competence measures were studied by means of the true change modeling procedures. Within the particular class of structural equation models, as put forward by Steyer et al. (1997, 2000), the true intraindividual change scores between successive occasions of measurement correspond to the values of endogenous latent variables. Various substantive hypotheses on the correlates and predictors of true change between the measurements can further be tested by use of such a model specification. The applicability of this class of models was demonstrated by the data on self-reported competence measures gathered in a sample of 312 preadolescents on four occasions within a two year period. The analyses of the developmental changes in perceived competence included testing the measurement models defined to represent the degree to which observed variations in competence measures were due to individual dispositions and/or to occasion-related influences. Further, in line with the assumptions of the latent state-trait theory, the models were specified to include the latent variables corresponding to the state variability and the trait change in perceived competence scores. By use of the true change modeling procedures the identified latent change variables were found to be related to students’ engagements in sports as well as to their sport and academic achievements.